Cell cycle activity of neural precursors in the diseased mammalian brain - Bragado Alonso, Sara; Schulze-Steikow, Max; Calegari, Federico (Frontiers in Neuroscience, 2014)
Basic research during embryonic development has led to the identification of general principles governing cell cycle progression, proliferation and differentiation of mammalian neural stem cells (NSC). These findings were recently translated to the adult brain in an attempt to identify the overall principles governing stemness in the two contexts and allowing us to manipulate the expansion of NSC for regenerative therapies. However, and despite a huge literature on embryonic neural precursors, very little is known about cell cycle parameters of adult neural, or any other somatic, stem cell. In this review, we briefly discuss the long journey of NSC research from embryonic development to adult homeostasis, aging and therapy with a specific focus on their quiescence and cell cycle length in physiological conditions and neurological disorders. Particular attention is given to a new important player in the field, oligodendrocyte progenitors, while discussing the limitation hampering further development in this challenging area.